Post a New Question

Math

posted by .

Can someone please check this for mistakes please?

y=4(x+3)-2x
y=4x+3-2x
y=2x+3
2x+3=y
2x=y-3
x=y/2-3

Hopefully I have rearranged the formula y=4(x+3)-2x to express x in terms of y.

  • Math -

    The first step is wrong
    4(x+3) does not equal 4x + 3.

  • Math -

    Y-4(X+3)-2X
    Y=4X+12-2X
    Y=2X+12
    2X=Y-12
    X=Y/2-6

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question